The broad-spectrum and ultra-sensitive detection of zeranol and its analogues by an enzyme-linked immunosorbent assay in cattle origin samples. Issue 35 (2nd June 2020) - Yin, Mengqi; Hu, Xiaofei; Sun, Yaning; Xing, Yunrui; Chai, Shujun; Xing, Guangxu; Yang, Yanyan; Teng, Man; Li, Qingmei; Wang, Yao; Deng, Ruiguang; Zhang, Gaiping
Abstract : This paper presents a broad-spectrum and ultra-sensitive ic-ELISA method for the rapid detection of zeranol and its analogues in cattle origin samples. Abstract : Zeranol (α-zearalanol) has been used as a growth promoter in livestock since 1969 in some non-EU countries; the residues of zeranol and its five analogues in animal origin foods may endanger human health due to their strong estrogenic and anabolic activities. Therefore, it is urgent to establish simple, rapid, real-time, broad-spectrum and high-sensitivity detection methods for the residues of zeranol and its analogues. In this study, an ultrasensitive indirect-competition enzyme-linked immunosorbent assay (ic-ELISA) was established for the rapid multi-residue detection of zeranol and its five analogues in cattle origin samples, which was based on a broad-spectrum monoclonal antibody (mAb) that specifically bound to zeranol and its analogues with high sensitivity. The half maximal inhibitory concentration (IC50 ) values for zeranol, β-zearalanol, zearalanone, α-zearalenol, β-zearalenol, and zearalenone were 0.103, 0.080, 0.161, 0.177, 0.254, and 0.194 ng mL −1, respectively, the recovery rates of cattle origin samples spiked with zeranol ranged from 79.2–104.2%, and the coefficient of variation (CV) values were less than 11.4%. Excellent correlation ( R 2 = 0.9845) was obtained between the results of HPLC-MS/MS and ic-ELISA. In conclusion, the developed ic-ELISA could be employed as an ultrasensitive and broad-spectrum detection method for monitoring trace ZEN residues in cattle origin foods.